The theoretical selectivity of N,N’-((1,3-phenylenebis(azanediyl))bis(carbonothioyl))bis(furan-2carboxamide) as an ionophore of selective electrode an ions Lead (II) - Mederos-Núñez, Yonatan; García-López, América; Arada-Pérez, María de los Ángeles (Revista Cubana de Química, 2021)
The present work calculates the likeness of the N, N’-((1, 3-fenilenbis theoretically (azanediil)) bis(carbonotioil)) bis(furan-2-carboxamida) as ionóforo of a selective electrode to ions lead (II). For it was calculated it the energy of union ionóforo-Pb2+, the same as for the main reported interferences: Cu2+, Hg2+, Zn2+, Ni2+, Co2+, Ca2+ and Cd2+. The geometries and energy were optimized using the Theory of the Functional one of the Density with the functional M06L and three combinations of different base groups. For the calculation of the solvation energy the pattern SMD was used. The relative energy obtained by the first two combinations of base groups differs with the experimental results. However, the third combination ratifies the experimental evidence of the preference of this ionóforo toward the ions Cu2+ and Pb2+ and the smallest selectivity toward the rest of the interferences, except for the ions Ni2+ whose relative energy are bigger than those of any other ion.